REDESAIN SIGN SYSTEM PADA KAWASAN OBYEK WISATA YANG INFORMATIF SEBAGAI USAHA UNTUK MEMBANGUN CITRA TEMPAT - Wirasasmita, Darin Nugraha; Swasty, Wirania (Jurnal Bahasa Rupa, 2020)
Sign system applied to the nature tourism object of Situ Gunung is still lacked in its placement, with conditions that are weathered, not maintained, not unity, and a less informative gate. In terms of design, the existing sign system in Situ Gunung nature tourism object is less in accordance with the theory of proper sign system.  Therefore, the authors are interested to redesign the sign system in Situ Gunung natural tourism object in Sukabumi Regency as an effort to build the image of the place by showing the identity of the place in the natural tourism object. The study used a qualitative approach by conducting various data collection techniques such as observation, interviews, and literature review.  The concept of the design is to bring out the tree of resin and fauna of the monkey Lutung as a characteristic element of the place of this natural tourism object.  The design of this signage is willing to make visitors easy to get information about the location and other information about the area of the tourist attraction